Immune and allergic responses to Anisakis pegreffii, with focus on the roles of IL-4, IL-13 and the IL-4 receptor alpha - Nieuwenhuizen, Natalie (Division of Immunology, 2014)
Includes bibliographical references (p. 117-127).